Framework Administered Account for Selected Fund Activities : Kingdom of the Netherlands-Netherlands Subaccount for Selected Fund Activities. (Policy Papers; Policy Paper ;, 2009)
The Fund, represented by the Managing Director, has reached understandings with the Kingdom of the Netherlands-Netherlands acting through the Ministry of Foreign Affairs, to finance capacity building, training and related activities. On the basis of these understandings, the Managing Director has established the essential terms and conditions of the Subaccount, with which the Kingdom of the Netherlands-Netherlands concurs, with respect to the nature, design, and implementation of the activities to be financed and the method by which the costs of the activities will be financed from the Subaccount.